Approaches to Improving Adherence to Secondary Prophylaxis for Rheumatic Fever and Rheumatic Heart Disease: A Literature Review with a Global Perspective. Issue 2 (March 2016) - Rémond, Marc G. W.; Coyle, Meaghan E.; Mills, Jane E.; Maguire, Graeme P.
Abstract : Acute rheumatic fever (ARF) and rheumatic heart disease (RHD) are autoimmune conditions resulting from infection with group A streptococcus. Current management of these conditions includes secondary antibiotic prevention. This comprises regular 3 to 4 weekly long-acting intramuscular benzathine penicillin injections. Secondary antibiotic prevention aims to protect individuals against reinfection with group A streptococcus, thereby preventing recurrent ARF and the risk of further damage to the heart valves. However, utilization of benzathine penicillin can be poor leaving patients at risk of avoidable and progressive heart damage. This review utilizes the Chronic Care Model as a framework to discuss initiatives to enhance the delivery of secondary antibiotic prophylaxis for ARF and RHD. Results from the search strategy utilized revealed that there is limited pertinent published evidence. The evidence that is available suggests that register/recall systems, dedicated health teams for delivery of secondary antibiotic prophylaxis, education about ARF and RHD, linkages with the community (particularly between health services and schools), and strong staff–patient relationships may be important. However, it is difficult to generalize findings from individual studies to other settings and high quality studies are lacking. Although secondary antibiotic prophylaxis is an effective treatment for those with ARF or RHD, the difficulties in implementing effective programs that reduce the burden of ARF and RHD demonstrates the importance of ongoing work in developing and evaluating research translation initiatives.